PEMBERDAYAAN REMAJA GAMPONG DALAM UPAYA PENCEGAHAN DAN PENGENDALIAN HIPERTENSI - Abdurrahman; Mutiah, Cut; Bustami; Amiruddin (Jurnal Pengabdian Masyarakat Sasambo, 2025)
Hypertension is the “Silent Killer” and a chronic diseases affecting not only the elderly but also adolescents. High blood pressure in adolescents is influenced by numerous factors, including age, height, gender, obesity, genetic predisposition, physical inactivity, smoking, and alcohol consumption. Hypertension control is a crucial aspect of Non-Communicable Diseases (NCDs) prevention and control. This community service initiative aims to train the “Remaja Gampong Peduli Hypertensi” as part of community empowerment effort within the Hypertension Prevention and Control Program in Karang Anyar Village, Langsa Baro Subdistrict, Langsa City. The implemented methods included team formation, adolescent health screening, training, mentoring, and monitoring and evaluation. The target audience comprises 20 adolescents aged 15–18 years. The implementation stages began with the formation on the RGPH team, followed bya pretest, education and training on the 6 Healthy Lifestyle Practices which form part of comprehensive hypertension management, and mentoring for the hypertension control program. The results showed a significant increase in respondent’s knowledge before and after education about adolescent hypertension and its prevention. During the pretest, only 25% of adolescents had good knowledge category, which increased to 85% after the educational sessions. Furthermore, 20% of adolescents had blood pressure >130/90mmHg, Body Mass Index data revealed that 30% of adolescents were obese, while 10% were categorized as overweight.